Profil Pasien Kanker Payudara di Rumah Sakit Onkologi Surabaya, 2014 - LUMINTANG, LOELITA MARCELIA; SUSANTO, ADI; GADRI, RAISSA; DJATMIKO, ARIO (Indonesian Journal of Cancer, 2015)
The prevalence of breast cancer in developing countries as well as developed countries still occupies in high level. The awareness of breast cancer risk factors can enhance the early detection program. The objective of this research is to achieve a complete description concerning risk factors: social, economy and demography statuses that will be advantageous for integrated prevention program ofÂ  breast cancer. This descriptive research used 485 datas out of 560 medical records that belonged to Rumah Sakit Onkologi Surabayaâs new breast cancer patients in 2014. The results of this research showed that 31.34% of breast cancer patients attained in the age of 41-50 years old and 51-60 years old; 41.65% acquired university education, 53.61% lived in Java; 69.69% did not have any history of cancer in their family; 85.36% did not have any history of breast cancer in their family; 57.31% were housewives; 42.27% obesity; 46.19% had been pregnant more than twice; 38.56% gave birth more than twice; 82.06% never used any contraception; 8.66% usedcontraception for 1-5 years; 63.71% breast-feeding; 27.84% breast-feeding to 3 or more children; and 21.03% breastfeeding for 0 to 6 months. There were some risk factors that are detectable and preventable.Â Prevalensi kanker payudara di negara berkembang dan negara maju masih sangat tinggi. Kesadaran akan faktor risiko kanker payudara dapat meningkatkan peluang untuk melakukan program deteksi dini. Penelitian ini bertujuan untuk mendapatkan gambaran yang lengkap perihal faktor risiko: status sosial, ekonomi, dan demografi yang akan bermanfaat untuk perencanaan program penanggulangan kanker terpadu. Penelitian deskriptif ini menggunakan 485 data dari 560 data rekam medis pasien kanker payudara baru 2014 di Rumah Sakit Onkologi, Surabaya. Hasil penelitian menunjukkan 31,34% pasien berusia 41â50 tahun dan 51â60 tahun; 41,65% berpendidikan universitas; 53,61% bertempat tinggal di Pulau Jawa; 69,69% tidak memiliki riwayat keluarga dengan kanker; 85,36% tidak memiliki riwayat keluarga dengankanker payudara; 57,31% ibu rumah tangga; 42,27% obesitas; 46,19% hamil lebih dari 2 kali; 38,56% melahirkan lebih dari 2 kali; 82,06% tidak pernah menggunakan kontrasepsi; 8,66% menggunakan kontrasepsi selama 1-5 tahun; 63,71% memiliki riwayat menyusui; 27,84% menyusui 3 anak atau lebih; dan 21,03% menyusui selama 0â6 bulan. Didapatkan sejumlah faktor risiko yang dapat diwaspadai serta dicegah.